Asuhan Keperawatan Pada An. Z dan An. S Dengan Demam Berdarah Dengue Grade I Di Ruang Amarylis Lantai 6 RSUD Khidmat Sehat Afiat Kota Depok - La Saudi; Sabrina Mutiara Rahmah (Indonesian Journal of Nursing Scientific, 2023)
ABSTRACT Background: Dengue Hemorrhagic Fever (DHF) is a disease transmitted by the Aedes aegypti mosquito which carries the dengue virus. Research Objectives: The research objective was to determine nursing care in An. Z and An. S with dengue hemorrhagic fever. Method: using a descriptive analytical case study method with a nursing care approach, literature study, data collection, and 2 patients An. Z and An. S with inclusion criteria: Child Patients at Khidmat Sehat Afiat Regional Hospital, Depok City, children who have been diagnosed with dengue hemorrhagic fever, children aged 3-14 years, children with a treatment period of 3x24 hours and exclusion criteria: Children who do not wish to undergo nursing assessment, children with incomplete medical record data. Results: After providing nursing care to An. Z and An. S with a diagnosis of dengue hemorrhagic fever. This nursing care is carried out 3x24 hours. On An. Z and An. S will be held from 05 to 07 April 2023 in the Amaryllis room on the 6th floor of Khidmat Sehat Afiat Hospital, Depok City. After nursing care was carried out for 3x24 hours, the results were obtained for An. Z The problem of ineffective thermoregulation has not been resolved because the temperature is 38̊C, N: 131 x/minute, the child's body feels warm, the risk of bleeding has not been resolved because the platelet value is still low at 119 10³/µL and Nausea the problem has not been resolved because the child has vomited once. Meanwhile in An. S obtained the results of all problems resolved in 3 diagnoses, namely ineffective thermoregulation, risk of bleeding and nausea. Conclusion: Nurses play an important role in dealing with problems that occur in children with dengue fever, by taking steps to prevent bleeding and providing education about the signs of bleeding and foods that can increase platelet levels can help the child's healing process.